The Installation of a Mini Line Hauler on a 9 Gt Handline Tuna Vessel in Southern Malang Sea, Indonesia - Rahmad Surya Hadi Saputra; Basino; Berbudi Wibowo; Ade Hermawan (Jurnal Penelitian Pendidikan IPA, 2025)
The tuna handlines operated by some fishers from Southern Malang in the Indian Ocean can be categorized as a type of static fishing gear. The stability of their small-sized vessels becomes critical when a large-sized tuna is caught by the handline and lifted with the help of a line hauler installed onboard, i.e., the floating angle tolerance may be exceeded.   This study aims to determine the angle of inclination of a 9 GT boat when a line hauler is operated onboard.  The research was carried out in June 2016 by measuring the principal dimensions of a fishing boat, FV Cahaya 01, in Pondok Dadap Fishing Port, Malang.  The principal dimensions are length overall (LOA), length before perpendicular (LPP), breadth (B), and depth (D) Data on the boat's principal dimensions, lines plan, and hull shape were used for the boat’s stability calculation.   The studied boat's buoyancy center is located at 0.27 m in front of the midship and the TCP is 0.315. The maximum load of the line hauler was 211.253 kg, and the inclination angle during the hauling process was 3.520.  The installation of the line hauler on the fishing boat creates a new acceptable stability of the boat.